Lessons from the Integrated Domestic Abuse Programme, for the implementation of Building Better Relationships. (June 2017) - Hughes, Will
This paper offers reflections on the Integrated Domestic Abuse Programme (IDAP), and its implications for the Building Better Relationships programme (BBR), which has now replaced IDAP as the main criminal justice intervention for male domestic violence perpetrators in England and Wales. While the BBR programme should be regarded with optimism, many of the principles underpinning IDAP are of ongoing relevance for practice with abusive men. There has been a tendency to distort IDAP and the broader Duluth model in discussions of interventions for perpetrators of domestic abuse. Although the BBR programme constitutes some changes of direction, its successful implementation requires continuity in the application of facilitator judgement, knowledge of group dynamics, non-judgemental dialogue, willingness to 'challenge', and responsiveness to individual service users.